Optimasi Search Engine Marketing (SEM) sebagai media komunikasi pemasaran: Studi pada PT Fortuna iMarks Trans - Asadiyah, Elia (Maliki Interdisciplinary Journal, 2024)
Technological developments cause challenges for businesses to compete fiercely. Marketing communication is one of the competitive strategies to increase sales, introduce products and increase brand awareness. One of the marketing communication strategies used in this case is search engine marketing (SEM). SEM as a marketing communication technique by utilizing the website to increase brand awareness. PT Fortuna iMarks Trans as one of the companies engaged in marketing consulting utilizes this strategy for its clients. As a result, clients who use SEM services from PT Fortuna iMarks Trans can increase brand awareness and increase sales of their products.